UPAYA PENCIPTA TERHADAP PELANGGARAN HAK EKONOMI ATAS CIPTAAN LAGU DI ERA DIGITAL - NIM. A1012211105, HAPSORO ARDHA PRADIPTA (Jurnal Fatwa Hukum, 2025)
ABSTRACT This study aims to determine the form of violation of economic rights over song creations in the digital era and to determine the efforts that have been made by creators in obtaining economic rights over their song creations that are re-sung and uploaded on social media applications without permission. The digital era has shown many works of creation that have been re-sung by others. However, the act of uploading a re-sung song has legal consequences related to aspects of copyright infringement if done without permission, because there are aspects of economic rights violations that are violated. The purpose of this study is to determine the form of violation of economic rights over song creations in the digital era and to determine the efforts that have been made by creators in obtaining economic rights over their song creations that are re-sung and uploaded on social media applications without permission. The results of the study indicate that the form of violation of economic rights over song creations in the digital era is downloading music through internet platforms, distributing other people's musical creations through internet platforms and recording music concerts and sharing them on internet platforms. The prohibition on duplicating copyright is regulated in Article 9 Paragraph (3) of Law of the Republic of Indonesia Number 28 of 2014 concerning Copyright. The distribution rights for musical creations have been protected in Article 9 Paragraph (1) Letter e of the Republic of Indonesia Law Number 28 of 2014 concerning Copyright. This full right is also strengthened in Article 40 Paragraph (1) Letter d of the Republic of Indonesia Law Number 28 of 2014 concerning Copyright, which states that protected creations include the fields of science, art and literature in the form of songs, or music with or without lyrics. Based on the provisions of the two articles, it is stated that the distribution of a creation without permission from the creator or copyright holder can be categorized as a copyright violation and can be prosecuted. The provisions of the articles in the field of music not only protect songs and their lyrics, but also the performers of the music. This protection is regulated in Article 23 Paragraph (2) of the Republic of Indonesia Law Number 28 of 2014 concerning Copyright. Meanwhile, efforts that have been made by the Creator or copyright holder can report to the Digital Platform (digital platform), the copyright holder can use the Copyright Claim feature or DMCA (Digital Millennium Copyright Act) takedown to delete or monetize the content. The efforts that have been made by the creator in obtaining economic rights to his song creations that are re-performed and uploaded on social media applications without permission are to file a copyright claim to the digital platform (digital platform) to get a share of the income from the musical work or request that the song be deleted. Keywords: Copyright, Violation of Economic Rights, Song Creations, Digital Era ABSTRAK Penelitian ini bertujuan untuk mengetahui bentuk pelanggaran hak ekonomi atas ciptaan lagu pada era digital dan mengetahui upaya yang telah dilakukan oleh pencipta dalam memperoleh hak ekonomi atas ciptaan lagunya yang dibawakan ulang dan diunggah di aplikasi sosial media tanpa izin. Era digitial telah memperlihatkan banyak karya ciptaan yang dinyanyikan ulang oleh orang lain. Namun, perbuatan mengunggah lagu yang dinyanyikan ulang tersebut memiliki konsekuensi hukum yang terkait aspek pelanggaran hak cipta jika dilakukan tanpa izin, sebab ada aspek pelanggaran hak ekonomi yang dilanggar. Tujuan penelitian ini adalah untuk mengetahui bentuk pelanggaran hak ekonomi atas ciptaan lagu pada era digital dan untuk mengetahui upaya yang telah dilakukan oleh pencipta dalam memperoleh hak ekonomi atas ciptaan lagunya yang dibawakan ulang dan diunggah di aplikasi sosial media tanpa izin. Hasil dari penelitian tersebut menunjukkan bahwa Bentuk pelanggaran hak ekonomi atas ciptaan lagu pada era digital yaitu mengunduh musik melalui platform internet, pendistribusian karya cipta musik orang lain melalui platform internet dan merekam konser musik dan membagikan ke platform internet. Larangan untuk melakukan penggandaan hak cipta diatur dalam Pasal 9 Ayat (3) Undang-Undang Republik Indonesia Nomor 28 Tahun 2014 tentang Hak Cipta. Hak pendistribusian terhadap karya cipta musik telah dilindungi dalam Pasal 9 Ayat (1) Huruf e Undang-Undang Republik Indonesia Nomor 28 Tahun 2014 tentang Hak Cipta. Hak penuh itu juga diperkuat dalam Pasal 40 Ayat (1) Huruf d Undang-Undang Republik Indonesia Nomor 28 Tahun 2014 tentang Hak Cipta yang menegaskan, bahwa ciptaan yang dilindungi, meliputi bidang ilmu pengetahuan, seni dan sastra yang berupa lagu, atau musik dengan atau tanpa teks. Berdasarkan ketentuan dua pasal tersebut ditegaskan, bahwa pendistribusian suatu ciptaan tanpa adanya izin dari pencipta atau pemegang hak cipta, dapat dikategorikan sebagai pelanggaran hak cipta, dan dapat dituntut secara hukum. Ketentuan pasal-pasal di bidang musik dalam tidak hanya melindungi lagu dan liriknya, tetapi juga para pelaku pertunjukan musik. Perlindungan tersebut diatur dalam Pasal 23 Ayat (2) Undang-Undang Republik Indonesia Nomor 28 Tahun 2014 tentang Hak Cipta. Sedangkan upaya yang telah dilakukan oleh Pencipta atau pemegang hak cipta dapat melaporkan ke Anjungan Digital (platform digital), pemegang hak cipta bisa menggunakan fitur Copyright Claim atau DMCA (Digital Millennium Copyright Act) takedown untuk menghapus atau memonetisasi konten tersebut. Adapun upaya yang telah dilakukan oleh pencipta dalam memperoleh hak ekonomi atas ciptaan lagunya yang dibawakan ulang dan diunggah di aplikasi sosial media tanpa izin adalah mengajukan klaim hak cipta (copyright claim) ke anjungan digital (platform digital) untuk mendapatkan bagian dari pendapatan karya musik atau meminta lagu dihapus. Kata Kunci : Hak Cipta, Pelanggaran Hak Ekonomi, Ciptaan Lagu, Era Digital